STRATEGI ADAPTASI BURUH PT. LIMBAH SAMPAH MENGHADAPI COVID-19 (Studi di Desa Nambo Kecamatan Klapanunggal Kabupaten Bogor Provinsi Jawa Barat) - Melliyatama Melliyatama; Yusnaini Yusnaini; Mery Yanti (Jurnal Media Sosiologi (JMS), 2021)
This study examined "labour adaptation strategy of PT. Limbah Sampah in Facing Covid-19 (Study at Nambo Village, Klapanunggal District, Bogor Regency, West Java Province)". The purpose of this study was to determine the socio-economic conditions and adaptation strategies of labour at PT. Limbah Sampah. in the face of current pandemic, Covid-19. The method used in this research was descriptive qualitative. Interview observations and documentation were data collection techniques used by researcher. This study used concept of survival strategy from Edi Suharto as analysis tool of the researcher. The results of this study showed that there were changes in the economic conditions of labourers at PT. Limbah Sampah during on going the Covid-19, both from the type of work and income level. Meanwhile, the survival strategy of PT. Limbah Sampah. was divided into three parts, first was active strategy by adding jobs such as collecting used goods, farming and raising livestock, in addition to adding work, family members also help in making a living such as assistance from their wives and children. The second was the passive strategy carried out by the labours, labours did minimize family expenses (living frugally) such as minimize food costs and minimize children's pocket money. The third was a network strategy where labours borrowed money and got social assistance from the government. As expressed by Edi Suharto which was defined as a person's ability to apply a set of ways to address various problems that surround their life. They used three (3) approaches, such as active strategy, passive strategy, and network strategy. .